Contribution to the knowledge of the cerambycid fauna (Coleoptera: Cerambycidae) of Tlaxcala, Mexico - Pérez-Flores, Oscar (Zootaxa, 2022)
In the present work specimens of the family Cerambycidae from the Colección Nacional de Insectos (CNIN, IBUNAM) were studied as well as recently collected specimens by author from Tlaxcala state, Mexico. Two new species are described and illustrated: Methia tlaxcalaensis sp. nov. Acanthocinus (Acanthocinus) andresi sp. nov. Moreover, Dexithea klugii (Laporte & Gory, 1836), Placosternus erythropus (Chevrolat, 1835), Heterachthes integripennis (Bates, 1885), Phoracantha recurva Newman, 1840, Acanthoderes (Pardalisia) funeraria Bates, 1861 and Aplagiognathus spinosus (Newman, 1840) are recorded for the first time from Tlaxcala state. The present study contributes to the knowledge of the longhorn beetles fauna of central Mexico.